Measurements of WH and ZH production in the H -> bb̄ decay channel in pp collisions at 13 TeV with the ATLAS detector - Aad, Georges; Andrei, George Victor; Bartels, Falk; Bolz, Arthur; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Jongmanns, Jan; Klassen, Martin; Krishnan, Anjali; et al. (The European physical journal. C, Particles and fields, 2021)
Measurements of the Standard Model Higgs boson decaying into a bb̄ pair and produced in association with a W or Z boson decaying into leptons, using proton-proton collision data collected between 2015 and 2018 by the ATLAS detector, are presented. The measurements use collisions produced by the Large Hadron Collider at a centre-of-mass energy of sqrt s = 13 TeV, corresponding to an integrated luminosity of 139 fb^-1. The production of a Higgs boson in association with a W or Z boson is established with observed (expected) significances of 4.0 (4.1) and 5.3 (5.1) standard deviations, respectively. Cross-sections of associated production of a Higgs boson decaying into bottom quark pairs with an electroweak gauge boson, W or Z, decaying into leptons are measured as a function of the gauge boson transverse momentum in kinematic fiducial volumes. The cross-section measurements are all consistent with the Standard Model expectations, and the total uncertainties vary from 30% in the high gauge boson transverse momentum regions to 85% in the low regions. Limits are subsequently set on the parameters of an effective Lagrangian sensitive to modifications of the WH and ZH processes as well as the Higgs boson decay into bb̄.
Gesehen am 20.01.2022